Potential Elimination of Human Gut Resistome by Exploiting the Benefits of Functional Foods - Tsigalou, Christina; Konstantinidis, Theocharis; Stavropoulou, Elisavet; Bezirtzoglou, Eugenia E.; Tsakris, Athanasios (Frontiers in Microbiology, 2020)
Recent advances in technology during the last decades strived to elucidate the diverse and abundant ecosystem of human microbiome. In particular theintestinal microbiota represents a densely inhabited environment which offers a plethora of beneficial effects to host’s well-being. On the other hand, it can serve as a potential reservoir of multi drug-resistant (MDR) bacteria and their antibiotic resistance genes (AR genes) comprising the ‘gut resistome’. AR genes are omnipresent for billions of years in the environment similarly to antibiotics. In the context of gut microbiome, these genes may conflate into exogenous MDR or emerge in commensals due to mutations or gene transfers. It is currently generally accepted, that Antimicrobial Resistance (AMR) poses a serious threat to public health worldwide. It is of paramount importance that researchers must focus, amongst other parameters, on elaborating strategies to manage gut resistome aiming the diminution of AMR. Potential interventions in gut microbiome by Fecal Microbiota Transplant (FMT) or functional foods, are newly emerged candidates for the uprooting of MDR strains and restoring dysbiosis and resilience. Probiotic nutrition is thought to diminish gut colonization from pathobionts. Yet only a few studies have explored the effects of antibiotic use on the reservoir of AR genes and the demanding time for return to normalby gut microbiota-targeted strategies. Regular administration of probiotic bacteria has been recently linked to restoration of gut ecosystem and decrease of gut resistome and AR genes carriers. This review summarizes the latest information about intestinal resistome and the proposed and intriguing ways of fighting against AMR through probiotic-based methods and gut microbial shifts.